Вплив високочастотного електромагнітного поля мобільного телефона на організм людини та метод захисту від нього - Савицька, Яна; Єршова, Ірина (Видавництво Національного університету «Львівська політехніка», 2009)
The influence of mobile telephone’s electromagnetic field of human’s being still one of the most urgents questions in the world of scientists. Today there are a lot of statistical researching results and ecommendations for protection and cureful using. Basic on experiments we worked out the program-apparatus individual or mass way of protection, which provides decreasing with more than 80% of electromagnetic field influence.
Keywords: electromagnetic field; mobile telephone; base station